APRESIASI TARI DAERAH SEBAGAI MEDIA PENDIDIKAN KARAKTER MAHASISWA PGMI UNIVERSITAS MUHAMMADIYAH MATARAM - Hasanah, Niswatun; Samrin, Samrin; Verliyanti, Verliyanti (Universitas Muhammadiyah Mataram, 2024)
Arts education is using art as a medium for character education for humans. However, there are still many who think that art is only for fun with no clear benefits. The use of art in higher education has not gone well considering the assumption that art, especially dance, is only related to movement skills. Unfortunately, it is assumed that women are better at dancing than men and that women are more